2001
DOI: 10.1007/s004250000475
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of plasma-membrane H + -ATPase and tonoplast-type pyrophosphatase in the plasma membrane of the sieve element-companion cell complex in the stem of Ricinus communis L.

Abstract: Plasma-membrane-located primary pumps were investigated in the sieve element (SE)-companion cell complex in the transport phloem of 2-week-old stems of Ricinus communis L. and, for comparison, in stems of Cucurbita pepo L. and in the secondary phloem of Agrobacterium tumefaciens-induced crown galls as a typical sink tissue. The plasma-membrane (PM) H+-ATPase and the tonoplast-type pyrophosphatase (PPase) were immunolocalized by epifluorescence and confocal laser scanning microscopy (CLSM) upon single or double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 25 publications
3
51
0
1
Order By: Relevance
“…Immunolocalization of PIN1 was performed using an affinity-purified rabbit anti-PIN1 antibody as described by Gälweiler et al (1998). Dilutions of primary anti-PIN2 guinea pig antibody (Ditengou et al, 2008) was 1:600 and for the anti-PM H + -ATPase rabbit antibody (Langhans et al, 2001; Agrisera AS07 260) 1:1000. As secondary antibodies, ALEXA Fluor 488 goat anti-guinea pig (Invitrogen) and ALEXA Fluor 555 goat anti-rabbit (Invitrogen) diluted to 1:600 were used.…”
Section: Histochemical Gus and Starch Staining And Immunolocalizationmentioning
confidence: 99%
“…Immunolocalization of PIN1 was performed using an affinity-purified rabbit anti-PIN1 antibody as described by Gälweiler et al (1998). Dilutions of primary anti-PIN2 guinea pig antibody (Ditengou et al, 2008) was 1:600 and for the anti-PM H + -ATPase rabbit antibody (Langhans et al, 2001; Agrisera AS07 260) 1:1000. As secondary antibodies, ALEXA Fluor 488 goat anti-guinea pig (Invitrogen) and ALEXA Fluor 555 goat anti-rabbit (Invitrogen) diluted to 1:600 were used.…”
Section: Histochemical Gus and Starch Staining And Immunolocalizationmentioning
confidence: 99%
“…Interestingly, double-labeling immunolocalizations showed the H + -PPase and the well-characterized P-type H + -ATPase in proximity at the PM of companion cells in Ricinus communis (Langhans et al, 2001). Langhans et al (2001) suggested that both H + pumps generate the PMF to maintain high Suc, K + , and amino acid concentrations in the phloem.…”
mentioning
confidence: 99%
“…Langhans et al (2001) suggested that both H + pumps generate the PMF to maintain high Suc, K + , and amino acid concentrations in the phloem. Coimmunogold labeling studies also showed that Arabidopsis (Arabidopsis thaliana) type I proton-pumping pyrophosphatase (AVP1) is localized at the PM of SE-CC complexes .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] However, H C -PPase also saliently localizes at the vascular tissues of plants, wherein this protein is predominantly localized at the plasma membrane (PM) of the sieve element companion cell (SE-CC) complexes. 8,[11][12][13] Thermodynamic, 14 genetic, immunohistochemical, and physiological evidence 8,15,16 is consistent with a reverse PPi synthase activity of H C -PPase at the PM in the phloem, where it plays an important role in PPi homeostasis and photosynthate partitioning. 10,[15][16][17] We contend that the magnitude of proton gradients associated with the tonoplast or PM location of this enzyme drives the protein's structurally congruent potential to work in a reversible manner -either in the synthesis or hydrolysis of its substrate, PPi.…”
mentioning
confidence: 60%